2008
DOI: 10.3892/or.19.5.1071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combining anti-epidermal growth factor receptor antibody C225 and radiation on DU145 prostate cancer

Abstract: Abstract. The epidermal growth factor receptor (EGFR) network has rich targets for prostate cancer killing. Herein we evaluated the effects of combining the EGFR inhibition and radiation on DU145 prostate cancer. We treated DU145 prostate cancer cells with various doses of anti-EGFR antibody (C225) and γ-irradiation (RAD). The effects of the treatment on cell viability and growth were assessed with cell counting, XTT and clonogenic assays. In vivo treatment effects were assessed using a subcutaneous tumor xeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…However, the suppression of colony formation in A431 cells was significantly increased by cetuximab alone treatment (SF 0.81, p < 0.001). Wagener et al showed that cetuximab increases the susceptibility of DU145 cells to radiation treatment, but the additional effect was not significant [17]. These results could not be fully verified in the colony formation assay carried out in this study.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…However, the suppression of colony formation in A431 cells was significantly increased by cetuximab alone treatment (SF 0.81, p < 0.001). Wagener et al showed that cetuximab increases the susceptibility of DU145 cells to radiation treatment, but the additional effect was not significant [17]. These results could not be fully verified in the colony formation assay carried out in this study.…”
Section: Discussioncontrasting
confidence: 67%
“…Therefore, an additional antiproliferative effect was only expected in the DU145 prostate carcinoma cell line by cetuximab [16]. In a report by Wagener et al and Liu et al a moderate suppressive effect on proliferation rate by either radiation or cetuximab alone has been observed in DU 145 prostate carcinoma cells which was more pronounced in combination [17,18].…”
Section: Introductionmentioning
confidence: 95%
“…The DU145 cell line is known to express EGFR and secrete EGF which acts via an autocrine method to stimulate growth (22). Inhibition of EGFR has been shown to enhance radiation response in a variety of cell lines including the DU145 cell line (23). It is possible that inhibition of this autocrine signaling pathway with AZD6244 treatment contributed to the observed increase in radiation sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies had shown that in addition to mitochondrial mediated reduction, other factors such as serum and membrane enzymes may also affect the bioreduction of tetrazolium compounds (Geys et al, 2010; Knight and Dancis, 2006; Kuhn et al, 2003). These factors may be responsible for the higher error reported by other laboratories (Wagener et al, 2008). …”
Section: Introductionmentioning
confidence: 90%